Impairments of working memory in schizophrenia and bipolar disorder: the effect of history of psychotic symptoms and different aspects of cognitive task demands - Frydecka, Dorota; Eissa, Abeer M.; Hewedi, Doaa H.; Ali, Manal; Drapała, Jarosław; Misiak, Błażej; Kłosińska, Ewa; Phillips, Joseph R.; Moustafa, Ahmed A. (Frontiers in Behavioral Neuroscience, 2014)
Comparisons of cognitive impairments between schizophrenia (SZ) and bipolar disorder (BPD) have produced mixed results. We applied different working memory (WM) measures (Digit Span Forward and Backward, Short-delay and Long-delay CPT-AX, N-back) to patients with SZ (n=23), psychotic BPD (n=19) and non-psychotic BPD (n=24), as well as to healthy controls (HC) (n=18) in order to compare the level of WM impairments across the groups. With respect to the less demanding WM measures (Digit Span Forward and Backward, Short-delay CPT-AX), there were no between-groups differences in cognitive performance; however, with respect to the more demanding WM measures (Long-delay CPT-AX, N-back), we observed that the groups with psychosis (SZ, psychotic BPD) did not differ from one another, but performed poorer than the group without history of psychosis (non-psychotic BPD). The history of psychotic symptoms may influence cognitive performance with respect to WM delay and load effects as measured by Long-delay CPT-AX and N-back tests respectively. We observed a positive correlation of WM performance with antipsychotic treatment and negative correlation with depressive symptoms in BPD and with negative symptoms in SZ subgroup. Our study suggests that WM dysfunctions are more closely related to the history of psychosis than to the diagnostic categories of SZ and BPD described by psychiatric classification systems.